József Herman, Linguistic Studies on Latin: selected papers from the 6th International Colloquium on Latin Linguistics, Budapest, 23-27 March 1991, Amsterdam-Philadelphia, 1994, 421 pp. (Minerva. Revista de Filología Clásica, 2019)
Reseña de József Herman, Linguistic Studies on Latin: selected papers from the 6th International Colloquium on Latin Linguistics, Budapest, 23-27 March 1991, Amsterdam-Philadelphia, 1994, 421 pp.